Proposed new interior design of cafe Nescafe for Nestle Malaysia at Cafe Village 6, University Teknologi Petronas, Bandar Baru Seri Iskandar, 31750 Tronoh, Perak Darul Ridzuan / Mai Nurul Akmar Mior Mokhtar - Mior Mokhtar, Mai Nurul Akmar (Faculty of Architecture, Planning and Surveying, 2011)
This final semester we are given a task either to proposed new interior design or upgrading project.I proposed a new interior design scheme of cafe Nescafe for Nestle Malaysia.The proposed site is at cafe Village 6 in University Teknologi Petronas,Perak.The idea of proposing a cafe is to provide a place where student can relax and gain knowledge at the same time.This project was followed by a few stages of progress. First is to collect information as much as possible about our client’s background,achievement,organisation and client mission and vission.Then it was followed by a strategic location as proposed site.Every stages is include with presentation.The stages goes by proposal stage then followed by planning stage and lastly final presentation.The project is completed when all this stages is complete.